2022
DOI: 10.1021/acs.est.2c02406
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation of FeS Nanoparticles Enhances Cr(VI) Sequestration

Abstract: Iron sulfide nanoparticles (nano-FeS) have shown great potential for in situ remediation of Cr(VI) pollution by reducing Cr(VI) to the less soluble and toxic Cr(III). However, material oxidation that inevitably occurs during storage and application alters its reactivity. Herein, we show that partial oxidation of nanoparticulate mackinawite (FeS) significantly enhances its capability in sequestering Cr(VI). Oxidation of nano-FeS increases its binding affinity to Cr(VI), likely due to preferential inner-sphere c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…It was reported that the surface FeS x generated by the sufidation of nZVI has lower band gaps than that of FeO x , leading to the redistribution of the electron charge density of S-nZVI by sulfur doping. 34 EIS results verify the above conclusion.…”
Section: Resultssupporting
confidence: 75%
“…It was reported that the surface FeS x generated by the sufidation of nZVI has lower band gaps than that of FeO x , leading to the redistribution of the electron charge density of S-nZVI by sulfur doping. 34 EIS results verify the above conclusion.…”
Section: Resultssupporting
confidence: 75%
“…The abnormal paucity of SO 4 2– is incongruous with the prevalence of REDOX reactions on the surface of Cr 0.5 Fe 0.5 (OH) 3 , but it does correspond to the decrease in the proportion of Cr(VI). The anomalous decrease in both SO 4 2– and Cr(VI) percentage might be attributed to the competitive adsorption of a significant amount of instantaneously formed CrO 4 2– and SO 4 . Both CrO 4 2– and SO 4 2– were desorbed from the surface of Cr 0.5 Fe 0.5 (OH) 3 . Subsequently, dissolved CrO 4 2– is reduced by dissolved sulfite under the catalysis of dissolved Fe(III) to form Cr(III) ions, which elucidates the notable release of Cr(III). SO 3 · + SO 3 · normalS 2 normalO 6 2 normalS 2 normalO 6 2 + normalH 2 …”
Section: Resultsmentioning
confidence: 98%
“…In fact, sulfite is widely present in soil, primarily due to bacterial growth on organosulfur compounds and chemolithotrophic growth on inorganic sulfur compounds . Additionally, the utilization of sulfur-containing reducing agents (such as Na 2 SO 3 , Na 2 S 2 O 4 , Na 2 S, FeS, , FeS 2 , and CaS x , ) significantly increases the sulfite content in soil. Our preliminary investigation revealed that the proportion of sulfite in total sulfur increased from 4.81% to 14.04% after 6 months of amorphous FeS 2 remediation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations